Application of the Class Management Approach in the Learning Process of Class 5A Students at SD Labschool UNNES Semarang City - Saputro, Nugroho Adhi; Deni Setiawan (Universitas Pendidikan Ganesha, 2025)
The problem of creating an effective and conducive learning environment is a major challenge for teachers, especially related to skills in classroom management. This study aims to describe the application of the classroom management approach, especially the recipe approach, and analyze its impact on the student learning process. This type of research is qualitative with a descriptive method. The subject of the study is a 5A class teacher at SD Labschool UNNES Semarang City who applies a recipe approach in learning activities. Data was collected through observation, interviews, and documentation, with instruments in the form of observation guidelines and interview guidelines. Data analysis was carried out in a qualitative descriptive manner with the stages of data reduction, data presentation, and conclusion drawn. The results showed that the application of the recipe approach in classroom management contributed significantly to the improvement of a positive classroom atmosphere and more orderly and cooperative student behavior. The conclusions of this study show that the recipe approach is effective in creating a learning environment that supports an optimal learning process. The implication of this study is the need for teachers to apply a structured and adaptive classroom management approach to improve the quality of learning and student development holistically.